Особливості передстартових психічних станів у спортсменів-лучників - Поляков, Ігор Олександрович; Павліченко, Д. Г. (Center of Modern Pedagogy "Learning Without Boarders", Canada, 2017)
У своїй статті автори проаналізували основні існуючі концептуальні підходи щодо визначення понять передстартових психічних станів у спорті. Авторами також було встановлено, що успішність та не успішність виступу спортсмена, впливає на виникнення або «апатії», або «бойової готовності». Автори у своїй статті виявили,що на успішний виступ спортсменів-лучників впливають наступні психологічні категорії: почуття обов’язку, мотивація / рівень домагань, вольові якості / «Я-концепція». Дослідження показали, що різні стрес-фактори по різному впливають на групи спортсменів та що невдалий виступ на змаганні може стати потужним стресогенним фактором і викликати навіть у талановитого спортсмена в майбутньому виникнення небажаних фізіологічних реакцій і невротичних розладів.

In their article, the authors analyzed the main existing conceptual approaches to determining the concepts of premature mental states in sports. The authors also found that the success and failure of the performance of the athlete, affects the emergence of either "apathy" or "combat readiness". The authors in their article found that the following performances of the athletes-archers are influenced by the following psychological categories: sense of duty, motivation / level of aspirations, volitional qualities / "I-concept". Studies have shown that various stress factors affect the athlete's groups in different ways, and that an unsuccessful performance on the competition can become a powerful stressor factor and even cause a gifted athlete in the future to develop unwanted physiological reactions and neurotic disorders.
Features pre-start mental states in athletes archers
Keywords: передстартові психічні стани; стрес-фактори; психологічні установки; спортсмени-лучники; pre-start mental conditions; stress-factors; psychological settings; athletes-archers